2017
DOI: 10.21577/0100-4042.20170091
|View full text |Cite
|
Sign up to set email alerts
|

Contaminantes emergentes em matrizes aquáticas do Brasil: cenário atual e aspectos analíticos, ecotoxicológicos e regulatórios

Abstract: publicado na web em 11/07/2017 EMERGING CONTAMINANTS IN AQUATIC MATRICES FROM BRAZIL: CURRENT SCENARIO AND ANALYTICAL, ECOTOXICOLOGICAL AND LEGISLATIONAL ASPECTS. Emerging contaminants occur in parts per trillion or less in aquatic matrices. The effects related to the exposure of aquatic biota and human to them have been identified for different compounds. The knowledge about the concentrations of the exposure is the first step to perform risk assessments. The present work describes a literature review about o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
57

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 113 publications
(163 reference statements)
2
31
0
57
Order By: Relevance
“…In the region of São Carlos (São Paulo), Campanha et al 39 reported an average value of 2 ng/L for 17β-estradiol in 24 positive data out of a total of 81 (30 %). Again, these results demonstrate the great variability of Brazilian surface waters concerning their degree of pollution, certainly influenced by sewage discharges, as pointed out earlier 1,42,60 . Data for MEC portrayed in Figure 3 can be used to perform a preliminary risk assessment on the presence of pharmaceuticals and personal care products in Brazilian surface waters using Equation 2, as well as PNEC data presented in Table 1.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In the region of São Carlos (São Paulo), Campanha et al 39 reported an average value of 2 ng/L for 17β-estradiol in 24 positive data out of a total of 81 (30 %). Again, these results demonstrate the great variability of Brazilian surface waters concerning their degree of pollution, certainly influenced by sewage discharges, as pointed out earlier 1,42,60 . Data for MEC portrayed in Figure 3 can be used to perform a preliminary risk assessment on the presence of pharmaceuticals and personal care products in Brazilian surface waters using Equation 2, as well as PNEC data presented in Table 1.…”
Section: Resultssupporting
confidence: 80%
“…In general, the levels of pharmaceuticals and personal hygiene products in Brazilian surface waters are higher than those found in other countries, as already reported in recent literature reviews 1,63 . Higher median concentrations are noticed for acetylsalicylic acid, followed by ibuprofen and 17α-ethinylestradiol.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Entre estes, os contaminantes emergentes compreendem fármacos e produtos de higiene pessoal, protetores solares, hormônios, entre outros (Richardson; Ternes, 2011). Tais contaminantes têm sido detectados nos diferentes compartimentos ambientais e podem apresentar efeitos adversos para a saúde humana ou ao ambiente, já que o estudo sobre esses ainda é recente e as legislações ambientais vigentes são deficitárias (Montagner et al, 2017).…”
Section: Introductionunclassified
“…Eclética Química Journal, vol. 44, n. 4, 2019, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] ISSN: 1678-4618 DOI: 10.26850/1678-4618eqj.v44.4.2019.p11-26 illicit drugs, pesticides, hormones and other compounds can be classified as emerging contaminants and the entry routes of these contaminants into the environment are diverse, coming from numerous sources, as it can be seen in Figure 1.…”
mentioning
confidence: 99%